The Relationship Between Patani Malay Greetings and Jambi Malay - Sidik, Solahuddeen; Waedoyee, Asmee (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to analyze the relationship between terms of address in Patani Malay and Jambi Malay in order to reveal similarities and differences as well as factors that influence the linguistic relationship between the two Malay languages. This is a qualitative study with a sociolinguistic approach. The focus of the study is the analysis of terms of address in Patani Malay (Yala) and Jambi Malay to examine their relationship and socio-cultural context. The research subjects are native speakers aged 40–70 years. Data collection for this study included: (1) participatory observation (natural interaction), (2) interviews (key informants), (3) document study (old manuscripts, dialect dictionaries), (4) instruments: semi-structured interview guide, observation sheet, written documents. The research sampling technique used purposive sampling (criteria: mastery of traditional greetings). Data were collected through literature study and participant observation, then analyzed based on vertical generation classification (upper [+3] to lower [-3]) and horizontal ([0]) as well as non-family contexts. Data analysis included data reduction, data presentation (comparative tables), triangulation of sources and experts, and interpretation (language migration theory and semantic change). Data validity included credibility, transferability, dependability, and confirmability. The results of the study show that both languages have parallel kinship address structures, especially in respect for the older generation (e.g., datok for grandfather) and the core kinship system, which reflects Malay cultural values.